Digital Text Books Based Multi Application: Does it Have Impact Towards Elementary Students Intelligence and Ecology Awareness? - Achmad Fanani; Cholifah Tur Rosidah; Triman Juniarso; Eldine Salsabila Putri; Gresya Ailina Roys; Vannilia (Universitas Pendidikan Ganesha, 2023)
Human concern and sensitivity to environmental problems is an entity of morality, behavior, and character. It cannot be built in humans instantly; the educational method is a strategic step to grow and improve the knowledge, skills, and behavior of individual humans as learners at an early age so that they become environmentally sound individuals with green behavior and a positive character. This study aims to develop multi-application-based digital teaching materials. This study uses a research and development design, with a 4D model consisting of define, design, develop, and disseminate stages. The research subjects were 5th-grade elementary school students. This type of research is developed with a 4D model. The method of data collection is done by distributing questionnaires. The data collection instrument is a questionnaire. Data analysis techniques using descriptive qualitative analysis, quantitative, and inferential statistics. The results showed that the mastery value of energy and ecological knowledge in the experimental class was 83% in the experimental class and 74% in the control class. These results prove that multi-application-based digital teaching materials impact students' intelligence and ecological awareness. Ecological awareness can be formed along with increased ecological understanding and intelligence.